Radykalne ugrupowania polityczne w Galicji na przykładzie ruchu ludowego i socjalistycznego - Szymański, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents the emergence, development and ideological profile of political groups operating in autonomous Galicia which can be described as “radical”. Criteria used in the introduction should be considered valid and reliable. In the case of agrarian movement the main objective of its creation and further operation was to transform property relations prevailing in the country, which was more or less associated with violation of property rights. The socialists proposed introduction of a system of state distribution of wealth and collective property instead of capitalist relations. This was associated not only with the total overvaluation of the existing socio-economic reality, but also the creation of a new man, free from economic coercion.
Keywords: historia Polski; Galicja; agraryzm; socjalizm